2010
DOI: 10.1038/npp.2010.8
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Stress, Serotonin Transporter Gene and Brain Structures in Major Depression

Abstract: The underlying neurobiology of major depression (MD) is likely to represent an interaction between genetic susceptibility and environmental factors such as stress. We investigated, in a multimodal high-resolution magnetic resonance imaging (MRI) genetic study, whether reduced hippocampal volumes and other brain alterations are associated with the tri-allelic polymorphism of the serotonin transporter and childhood stress in patients with MD and healthy subjects. Patients with MD and healthy participants were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
106
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(119 citation statements)
references
References 58 publications
(57 reference statements)
10
106
2
Order By: Relevance
“…Within the 1.5T cohort we indeed found that persons with a history of CA showed a reduction of gray matter in the orbital prefrontal cortex as compared to persons without CA. This finding could, however, not be replicated within the 3T cohort and it remains therefore unclear whether this was a false positive finding or whether this non-replication was caused by higher levels of image distortion and signal 14 dropout at 3T, which particularly affect the orbitofrontal and anterior temporal areas.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Within the 1.5T cohort we indeed found that persons with a history of CA showed a reduction of gray matter in the orbital prefrontal cortex as compared to persons without CA. This finding could, however, not be replicated within the 3T cohort and it remains therefore unclear whether this was a false positive finding or whether this non-replication was caused by higher levels of image distortion and signal 14 dropout at 3T, which particularly affect the orbitofrontal and anterior temporal areas.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, numerous studies have shown that persons with a specific genetic make-up are more prone to develop stress-related mental disorders after experiencing major life events like CA (11)(12)(13). Moreover, recent studies suggest that gene by stress interactions may be involved in inter-individual differences in local brain volume (14) and may also play a role in the onset of several psychiatric disorders, like bipolar disorder, schizophrenia, attention deficit hyperactivity disorder and depression (for review see (15)). In case of depression it has been suggested that gene by stress interactions may explain up to 60-70 % of the variance in disease susceptibility (16).…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal size was shown to be highly heritable (Stein et al, 2012), and several reports on genetic variations influencing shape alterations in the hippocampus support the hypothesis of hippocampal volume reductions as a predisposing trait of MDD (Frodl et al, 2008(Frodl et al, , 2010aStein et al, 2012). This concept of trait-related limbic aberrations further leans on studies revealing reduced hippocampal volumes in depressed to be independent of severity of depressive symptoms, age at onset, and duration of illness (Frodl et al, 2002), as it is also the case in our (Arnone et al, 2013;Nordanskog et al, 2010).…”
Section: Discussionmentioning
confidence: 87%
“…Frodl and colleagues reported smaller hippocampal volumes in short allele carriers versus long allele carriers that experienced early life emotional neglect [71]. More recently, a prospective longitudinal study of 174 participants revealed an association between short alleles and smaller right hippocampal volume (Little et al, 2015) [13].…”
Section: The Role Of Affective Functioningmentioning
confidence: 99%
“…The hippocampus is functionally important for long-term memory storage of episodic events as well as emotion and mood regulation [69]. A number of studies have linked hippocampal abnormalities with early life stress and depression [70][71][72][73]. Evidence suggests 5-HTTLPR may play an important role in explaining this relationship.…”
Section: The Role Of Affective Functioningmentioning
confidence: 99%